2007
DOI: 10.1073/pnas.0701953104
|View full text |Cite
|
Sign up to set email alerts
|

Cellular senescence is an important mechanism of tumor regression upon c-Myc inactivation

Abstract: Oncogene-induced senescence is an important mechanism by which normal cells are restrained from malignant transformation. Here we report that the suppression of the c-Myc (MYC) oncogene induces cellular senescence in diverse tumor types including lymphoma, osteosarcoma, and hepatocellular carcinoma. MYC inactivation was associated with prototypical markers of senescence, including acidic ␤-gal staining, induction of p16INK4a, and p15INK4b expression. Moreover, MYC inactivation induced global changes in chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
366
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(387 citation statements)
references
References 47 publications
21
366
0
Order By: Relevance
“…Consistent with the two-step hypothesis for senescence and immortalization [7], It has been experimentally shown that senescence is not only a potent defense against cancer [9][10][11][12][13][14], but that cancer cells that have escaped senescence can be reversed to senescence by restoration of the tumor suppressor p53 [15,16]. It is thus widely believed that senescence and immortalization share some common biology, and telomeres and telomerase may be the connection [17].…”
Section: Introductionmentioning
confidence: 59%
“…Consistent with the two-step hypothesis for senescence and immortalization [7], It has been experimentally shown that senescence is not only a potent defense against cancer [9][10][11][12][13][14], but that cancer cells that have escaped senescence can be reversed to senescence by restoration of the tumor suppressor p53 [15,16]. It is thus widely believed that senescence and immortalization share some common biology, and telomeres and telomerase may be the connection [17].…”
Section: Introductionmentioning
confidence: 59%
“…Consistently, we observed that HeLa cells occurred senescence when the integrated HPV fragment was removed. Considering the phenomenon that the expression of MYC was dramatically reduced when the HPV knockout, we postulated that the cell senescence might be related to the significant downregulation of MYC expression, which had been proved to play a crucial role of integrated HPV in cervical cancer cell growth 17. But we also noticed that the double knockout of 8q24.22 region could not induce obvious senescence in HeLa cells, although it lead to about 50% decrease of MYC expression.…”
Section: Discussionmentioning
confidence: 87%
“…Hydroxyurea, resveratrol, and pyrithione induce premature senescence by ROS generation (Luo et al 2013;Ong et al 2011). Thus, drug targeting premature senescence in cancer cells could be a superior approach rather activating apoptosis because at a lower concentration of the drug, activated senescence regresses the tumor growth by neutralizing the toxicity of the drugs (Wu et al 2007). Of note, senescence can be an alternative route to curb tumor growth where cells get resistance to apoptosis.…”
Section: Discussionmentioning
confidence: 99%